1974
DOI: 10.1021/j100609a002
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of external activation systems with multiple isomerizations and decompositions

Abstract: A general method for the steady-state analysis of complex external activation systems with multiple isomerization and decompositions is developed. This method is used for both "strong" and "weak" collisions. The algorithm for such an analysis is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1974
1974
2005
2005

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…Various solutions for the steady-state equations have been reported [47,48,50,51]; in this work an iterative procedure [50] was used in that each iteration corresponds to the time between collisions: The population is distributed according to the probabilities for collisions and reaction. The stabilization and decomposition products are accumulated until S 1 ϩ S 2 ϩ D 1 ϩ DЈ has converged to the initial population.…”
Section: F(e) ϭ Kј(e)b(e)/⌺kј(e)b(e)mentioning
confidence: 99%
“…Various solutions for the steady-state equations have been reported [47,48,50,51]; in this work an iterative procedure [50] was used in that each iteration corresponds to the time between collisions: The population is distributed according to the probabilities for collisions and reaction. The stabilization and decomposition products are accumulated until S 1 ϩ S 2 ϩ D 1 ϩ DЈ has converged to the initial population.…”
Section: F(e) ϭ Kј(e)b(e)/⌺kј(e)b(e)mentioning
confidence: 99%
“…The yields of S and D are computed by solving the master equation with the appropriate model for P ( E ‘, E ) and RRKM theory for the k ( E )'s . If the experiments are in the high-pressure region, then a simple correction to the strong collision model may be used …”
Section: Approachesmentioning
confidence: 99%
“…The energy transfer model for the collisional stabilization of the excited radicals is also needed in the calculation. 25 Heptane was assumed to be a strong collider. Energy transfer involving weak colliders is specified by probabilities of the excited species going from one energy state to another upon collision.…”
Section: Reactionmentioning
confidence: 99%
“…Energy transfer involving weak colliders is specified by probabilities of the excited species going from one energy state to another upon collision. [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] In these calculations, collision with hydrogen was assumed to be described by a step ladder model with a step size of 400 cm-1 (1.144 kcal/mol), and nitrogen by a step ladder model with a step size of 800 cm-1 (2.29 kcal/mol).22 (A step ladder model assumes that upon collision the amount of energy transferred is always equal to the step size.) It was found that if energy transfer in hydrogen was described by an exponential model with average transferred energy = 525 cm"1 IIIII*V(1.50 kcal/mol) exactly the same ratios were obtained as with the step ladder model, despite the significantly different energy transfer probabilities obtained by the two models.…”
Section: Reactionmentioning
confidence: 99%
See 1 more Smart Citation